Suppose a polynomial
p
(
x
)
such that it has a the following properties:
- Leaves a remainder
a
on division by
(
x
−
a
)
,
- Leaves a remainder
b
on division by
(
x
−
b
)
,
- Leaves a remainder
c
on division by
(
x
−
c
)
.
Find the remainder when p ( x ) is divided by ( x − a ) ( x − b ) ( x − c ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice standard approach. Can you generalize this? That is to say:
Prove that for positive integers k = 1 , 2 , 3 , … , n , suppose a polynomial p ( x ) has the properties that it leaves a remainder a k when divided by ( x − a k ) , then k = 1 ∏ n ( x − a k ) divides ( p ( x ) − x ) .
Thanks For the solution! + 0 ! from me :D
Challenge Master:
I'll assume that the a k are real numbers, not functions. From the Remainder Theorem, we have that p ( a k ) = a k . Let q ( x ) = p ( x ) − x . Then, since q ( a k ) = p ( a k ) − a k = 0 , some of the roots of q ( x ) are the a k . Thus, q ( x ) = r ( x ) ∏ k = 1 n ( x − a k ) , for some polynomial r ( x ) . Replacing the left hand side, we get p ( x ) − x = r ( x ) ∏ k = 1 n ( x − a k ) . Therefore, ∏ k = 1 n ( x − a k ) divides p ( x ) − x evenly.
One can pretty quickly realize that such a polynomial p(x) can equal x. The remainder of x/(x-a)(x-b)(x-c) is clearly x, and that's your answer.
Problem Loading...
Note Loading...
Set Loading...
From the Remainder Theorem, we have p ( a ) = a , p ( b ) = b , p ( c ) = c . Define q ( x ) = p ( x ) − x . Then, q ( a ) = q ( b ) = q ( c ) = 0 i.e. a , b , c are roots of q ( x ) . Thus, q ( x ) can be factored as ( x − a ) ( x − b ) ( x − c ) r ( x ) , for some polynomial r ( x ) . Substituting back, we have p ( x ) − x = ( x − a ) ( x − b ) ( x − c ) r ( x ) , or p ( x ) = ( x − a ) ( x − b ) ( x − c ) r ( x ) + x . This, when divided by ( x − a ) ( x − b ) ( x − c ) , has remainder x .